Avant-Garde, Internationalism, and Politics : Argentine Art in the Sixties - Giunta, Andrea (Book collections on Project MUSE., 2007)
An exploration of the impact of the 1960s and the U.S. post-cold war moment on the reception of Latin American art and artists.